PERAN PEMBELAJARAN BERBASIS PROYEK DALAM MENINGKATKAN PEMAHAMAN NILAI-NILAI SOSIAL MURID KELAS V SD GMIT NO 7 OEBUFU PADA KURIKULUM MERDEKA - Natalia Saban, Serlin; Treesly Y.N Adoe; Martha Khristina Kota (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the role of Project-Based Learning in improving students’ understanding of social values within the Merdeka Curriculum at SD GMIT No. 7 Oebufu, Kupang City. This study employed a qualitative approach with a descriptive method. The research subjects were fifth-grade students of SD GMIT No. 7 Oebufu in the 2025/2026 academic year. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The results showed that Project-Based Learning plays a role in enhancing students’ understanding of social values. The value of cooperation was reflected in students’ collaboration during project completion and group presentations. The value of responsibility was demonstrated through students’ ability to complete tasks according to their assigned roles, while social care was reflected in students’ willingness to help one another and respect their peers’ opinions. Therefore, Project-Based Learning contributes positively to the development of students’ social values in accordance with the objectives of the Merdeka Curriculum. Keywords: Project-Based Learning, Social Values, Merdeka Curriculum.